DAYA TERIMA DAN KANDUNGAN SERAT BAKSO IKAN DENGAN SUBSTITUSI PISANG KEPOK - Lydia Fanny; Thresia Dewi Kartini; Yulinar Yulinar (Jurusan Gizi Poltekkes Kemenkes Makassar, 2022)
Bakso is a food that is very popular among Indonesian people from children, teenagers to adults because it has a delicious taste and is easy to find. Fish balls are round foods made from tapioca flour and snapper. Fish meatballs with kepok banana substitution are an alternative product that is high in fiber nutritional value and does not leave the unique taste of fish balls. This study aims to determine the acceptability and fiber content of fish balls with kepok banana substitution. This research is a pre- experimental research. Fiber content was tested using the gravimetric method. Data and results are presented in the form of tables and narratives. The results of the acceptability test from the aspect of color, texture and taste in the most preferred 40 gram banana kepok fish ball substitution. The most preferred aroma aspect is fish ball substitution with banana kepok 30 grams. The results of the fiber content test showed that there was an increase in fiber content of 14.97% in the 50 gram substitution compared to fish balls without kepok banana substitution. It is recommended that further research can analyze the content of other nutrients and acceptance to the target, namely obese adolescents.